2020
DOI: 10.1021/acs.jafc.0c01302
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Propionate Attenuates the Lipopolysaccharide-Induced Epithelial–Mesenchymal Transition via the PI3K/Akt/mTOR Signaling Pathway

Abstract: Short-chain fatty acids (SCFAs), especially propionate, originate from the fermentation of dietary fiber in the gut and play a key role in inhibiting pulmonary inflammation. Chronic inflammation may induce an epithelial–mesenchymal transition (EMT) in alveolar epithelial cells and result in fibrotic disorders. This study was designed to investigate the beneficial effect of sodium propionate (SP) on lipopolysaccharide (LPS)-induced EMT. In cultured BEAS-2B cells, the protein expression levels of E-cadherin, α-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…Studies have shown that activation of the PI3K/Akt/mTOR pathway in human umbilical cord mesenchymal stem cell (UC‐MSC)‐derived exosomes exerts antiapoptotic effects on rat cardiomyocytes (H9C2) (Liu et al, 2019). Likewise, sodium propionate suppresses the PI3K/Akt/mTOR signaling pathway attenuating the inflammation induced by LPS (Chen et al, 2020). We found that the BeSO 4 ‐Exos treated RAW 264.7 cells upregulated LDH activity and the inflammatory response, whereas pretreatment with rapamycin alleviated it.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that activation of the PI3K/Akt/mTOR pathway in human umbilical cord mesenchymal stem cell (UC‐MSC)‐derived exosomes exerts antiapoptotic effects on rat cardiomyocytes (H9C2) (Liu et al, 2019). Likewise, sodium propionate suppresses the PI3K/Akt/mTOR signaling pathway attenuating the inflammation induced by LPS (Chen et al, 2020). We found that the BeSO 4 ‐Exos treated RAW 264.7 cells upregulated LDH activity and the inflammatory response, whereas pretreatment with rapamycin alleviated it.…”
Section: Discussionmentioning
confidence: 99%
“…LPS induces airway-centered inflammation and airway fibrosis and remodeling (Takahagi et al, 2020). According to recent studies, LPS induces EMT in BEAS-2B cells and mouse models, which are characterized by a decrease in E-cadherin levels, increased levels of α-SMA, vimentin, MMP2, and MMP9 proteins, and inflammatory response, leading to extracellular matrix deposition and lung fibrosis (Chen et al, 2020). TGF-β1 is a key growth factor involved in inducing inflammatory processes and EMT.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a mesenchymal-like transformation was not observed until 7 d after the LPS induction. However, other cells showed significant morphological changes after 24–72 h of LPS treatment [ 25 , 26 ]. This result is related to the levels of inflammatory factors secreted by the mammary epithelial cells.…”
Section: Discussionmentioning
confidence: 99%